Serotyping for Homotransplantation. XXII, Specificity of Cytotoxic Antibodies Developing after Renal Transplantation - Morris, P. J. (1969)
Cytotoxic antibodies against allogeneic lymphocytes were detected in 13 patients after removal of a renal allograft. Antibodies were not detected in seven patients who had grafts in situ for less than two months, but were detected in 13 out of 17 patients who had grafts in situ for longer than two months. The HL-A specificity of these positive sera was compatible with the HL-A antigen mismatch of the donor-recipient pairs in most instances, providing further evidence that such antibodies result from direct sensitization by the allograft and may play some part in renal allograft rejection.